Thematic Progression in Reading Texts of an Arabic Textbook for Senior High School - Gandari, Amanda Marwah; Tatang, Tatang (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze thematic progression patterns, assess text coherence, and interpret the potential comprehensibility of reading passages in the Grade 10 Arabic textbook for Senior High School published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020. The study adopted a qualitative approach using a discourse analysis design grounded in the Systemic Functional Linguistics (SFL) framework. The data comprised five reading passages purposively selected from the textbook. Data were collected through document analysis and examined by identifying thematic progression patterns across sentences, evaluating the level of coherence, and interpreting the potential comprehensibility of the texts. The analysis identified 75 thematic progression relations, with Constant Progression at 57.33% and Split Rheme Progression at 20% the most prevalent. According to the results, three of the texts classified as Good showed a more consistent flow of information and were deemed to have a higher probability of cohering, while the two classified as Fair displayed patterns of thematic progression that were more varied, probably making it necessary for readers to put in greater inferential effort to establish connections across sentences. The findings suggest that thematic progression patterns should be considered when developing and evaluating Arabic reading materials to enhance text coherence and support students' reading comprehension.